Clinical characteristics and short-term outcomes of Japanese encephalitis in pediatric and adult patients: a retrospective study in Northern China - Zhang, Fangyuan; Xu, Guangyin; Zhang, Xiaoyu; Li, Yue; Li, Dong; Wang, Chunjuan; Guo, Shougang (Frontiers in Neurology, 2023)
The study was to compare the clinical characteristics and short-term outcome of pediatric and adult Japanese encephalitis (JE) patients, to find out the differences. The retrospective study consists of 107 patients (62 pediatric patients and 45 adult patients) with JE. Clinical characteristics and short-term outcome were analyzed. The short-term outcome of each patient was defined as good outcome or poor outcome according to their Glasgow Coma Scale (GCS) scores (GCS >8 vs.≤8) at discharge. As for acute complications, the incidence of pulmonary infection was higher in 25 adults (25/45,55.6%) than in 19 children (19/62,30.6%; P=0.01). Upper gastrointestinal bleeding was more common in 10 patients with pulmonary infection (10/44,22.7%) than in 1 patient without pulmonary infection (1/63,1.6%; P=0.001). The proportion of mechanical ventilation and admission to the intensive care unit (ICU) for supportive care were higher in patients with pulmonary infection than patients without infection (P＜0.001, P=0.008, respectively). The GCS scores at discharge in patients with pulmonary infection (7,4-12.75) was lower than patients without pulmonary infection (14,10-14; P＜0.001). Although the GCS scores at admission of children (9.5,7-13) was similar to that of adults (7,6-13), the GCS scores at discharge of adults (7,3.5-13) was lower than that of children (13,10.75-14; P＜0.001). The short-term outcome of JE was worse in adults. Pulmonary infection was correlated with high incidence of upper gastrointestinal bleeding, mechanical ventilation, ICU hospitalization in JE. Pulmonary infection is a prognostic predictor of short-term outcome in patients with JE. Vaccination for adults should be initiated.